Criaturas no humanas y reinado de Dios. La dimensión ecológica del mensaje de Jesús - Pericás, Esther Miquel (Cauriensia, 2022)
The main thesis of this paper is that Jesus conceived God’s kingdom as including non-human creatures. This idea has its roots in the Hebrew Bible, most conspicuously in the Book of Psalms, and in Ancient Jewish thought, where the relation between God and all created beings corresponds to that between a king and his subjects. The interpretative approach sponsored by the Ontological turn in Anthropology has allowed us to understand this correspondence in a literal sense, and to acknowledge the interpersonal character that Biblical thought ascribes to the relation between God and his non-human creatures.